2007
DOI: 10.1016/j.atmosenv.2007.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Fungal fragments in moldy houses: A field study in homes in New Orleans and Southern Ohio

Abstract: Smaller-sized fungal fragments (<1 μm) may contribute to mold-related health effects. Previous laboratory-based studies have shown that the number concentration of fungal fragments can be up to 500 times higher than that of fungal spores, but this has not yet been confirmed in a field study due to lack of suitable methodology. We have recently developed a field-compatible method for the sampling and analysis of airborne fungal fragments. The new methodology was utilized for characterizing fungal fragment expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 27 publications
6
81
7
Order By: Relevance
“…This difference may be associated to the assay efficiency or the size range that was wider in the present study. Other studies that focused on the occurrence of submicronic fragments in mold-contaminated indoor or outdoor air used methods to detect ␤-glucan (14,16,18,47) and NAHA (21) as biomarkers of fungal fragments in size-fractionated samples. However, these studies were limited by the imprecise fractionation of particles due to confounding variables such as spore bounce (18,47,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be associated to the assay efficiency or the size range that was wider in the present study. Other studies that focused on the occurrence of submicronic fragments in mold-contaminated indoor or outdoor air used methods to detect ␤-glucan (14,16,18,47) and NAHA (21) as biomarkers of fungal fragments in size-fractionated samples. However, these studies were limited by the imprecise fractionation of particles due to confounding variables such as spore bounce (18,47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Methodological advances have been made in a number of studies by using fungal membrane constituents such as ergosterol, phospholipid fatty acids, and (1¡3)-␤-D-glucans to demonstrate the presence of fungal biomass in size-fractionated fungal aerosols (9)(10)(11)(12)(13)(14)(15)(16). Further, sugar alcohols (arabitol and mannitol) (17), enzymes (N-acetyl hexosaminidase and N-acetyl-D-glucosaminidase) (18)(19)(20)(21)(22), antigens, allergens (23)(24)(25)(26), and DNA (27)(28)(29) have been used as proxies for total fungal exposure or occurrence of airborne fungal particles.…”
mentioning
confidence: 99%
“…Of the mold particulates the greatest concern is the nano-particulates at or less than 0.3 microns shed from mold colonies. Field studies of water-damaged homes have shown concentrations of nano-particulates in indoor dust that are at least 1000 times or greater than the indoor air mold spore counts [12][13][14][15][16][17][18]. These particulates contain 1, 3-beta glucans, a variety of fungal proteins that include substrate enzymes as well as mycotoxins.…”
Section: Particulatesmentioning
confidence: 99%
“…It is associated with nano-particulates shed by mold that contain 1, 3-beta glucans, mycotoxins and a variety of antigenic proteins [14,21,25,[48][49][50][51][52][53][54][55].…”
Section: Sarcoidosismentioning
confidence: 99%
See 1 more Smart Citation